APnet, an innovative multidisciplinary medical information platform for acute pancreatitis - Yang Fei (Revista da Associação Médica Brasileira)
SUMMARY The APnet information platform aims at assisting patients suffering from acute pancreatitis, health professionals and patients' relatives in the acute pancreatitis care pathway by providing an integrated information system. The system consists of a mobile platform and a Clinical Information System. The system is currently on the formal operation phase focusing on addressing the needs of citizens of China.